Social bots spoil activist sentiment without eroding engagement - Linda Li; Orsolya Vásárhelyi; Balázs Vedres (Scientific Reports)
Abstract Social bots are highly active on social media platforms, significantly affecting online discourse. We analyzed the dynamic nature of bot engagement related to Extinction Rebellion climate change protests in 2019. We found bots to impact human behavior more than the other way around during active discussions. To assess the causal impact of bot encounters, we compared communication histories of those who interacted with bots with matched users who did not. There is a consistent negative impact of bot encounters on subsequent sentiment. The impact on sentiment is conditional on the user’s original support level, with a more negative impact on those with a favourable or neutral stance towards climate activism. Political ’astroturfing’ bots induce an increase in human communications, while encounters with other bots result in a decrease. Bot encounters do not change activists’ engagement levels in climate activism. Despite the seemingly minor impact of individual bot encounters, the cumulative effect is profound due to the large volume of bot communication. Our findings underscore the importance of monitoring the influence of social bots, as with new technological advancements distinguishing between bots and humans becomes ever more challenging.